Chekkurmanis is a mineral-rich leafy green - Verma, Arti; Sood, Sonia (Indian Horticulture, 2018)
Promotion of perennial crops is a good alternative for food security since they offer more consistent, and year round production without any break. Chekkurmanis or sweet leaf (Sauropus androgynus) is such nutritive perennial green that can be easily grown in hot and humid tropical climate. People consume it in the form of leafy vegetable. It occupies a prominent place in almost each and every household kitchen garden in Kerala. Its plants have high nutritive value and that is why it is nicknamed as ‘multi vitamin green’ and ‘multi mineral packed leafy vegetable’.